The consumption pattern and perception of using artificial sweeteners among the public in Tabuk region, Saudi Arabia - Alharthi, Sawsan A. S.; Alaisayi, Khulud Hassan A.; Alalawi, Lina Yousef S.; Alamri, Raniya Omar S.; Abu-Elfotuh, Karema; Alenazi, Tahani S.; Amirthalingam, Palanisamy; Albariqi, Hassan A. H.; Mohammed, Asmaa A.; Alsubayti, Norah; Hamdan, Ahmed M. E.; Kozman, Magy R. (Frontiers in Public Health, 2023)
Background: Obesity and weight gain have become the major problems worldwide. Thus, several forms of alternative intense sweeteners are extensively used offering non-caloric sweet taste. According to our best of knowledge, no research has studied neither the consumption pattern not the perception of using artificial sweeteners in Saudi Arabia yet. Objectives: Our research aimed to study the usage pattern of such artificial sweeteners in Tabuk region and to estimate the knowledge and attitudes of their usage among population. Methods: A cross-sectional study promoted on multiple social media platforms and face-to-face interview in different malls and hospitals in Tabuk region. We grouped participants into two major groups; the users and the non-users of artificial sweeteners. Each group has been subdivided into healthy and medically recorded subgroups. Participants' characteristics and their choice of sweeteners were analyzed by bivariate analysis. The age, gender, and education level of the participants were adjusted using binary logistic regression in order to adjust potential confounders. Results: A total 2760 participants were included in our study. We found that more than 59% of the participants having over 45 years old were non-hospitalized irrespective to usage of artificial sweeteners. Besides, females, graduates, diabetics were significantly high irrespective to their subgroup. Moreover, steviana is the most commonly used artificial sweetener. In addition to, healthy participants showed higher perception towards usage and adverse effects of artificial sweeteners. Furthermore, bivariate analysis using logistic regression revealed significant associations (p < 0.05) with confounders such as gender, age, and education level. Conclusion: The educational programs and nutritional advise for the safe consumption and the daily permissible doses of artificial sweeteners are essential and should be directed specifically for females.